Gastrointestinal Symptoms of Patients with Fabry Disease - Licia Pensabene; Simona Sestito; Angela Nicoletti; Francesca Graziano; Pietro Strisciuglio; Daniela Concolino (Gastroenterology Research and Practice, 2016)
In order to characterize gastrointestinal (GI) symptoms of 50 patients with Fabry disease (FD) (22 M; age range: 4–70 y; 35 adults and 15 children), validated questionnaires of GI symptoms were used to diagnose the functional gastrointestinal disorders (FGIDs) of the patients with GI symptoms (33/50 (66%); 25/35 adults and 8/15 children) according to Rome III criteria. In 16/25 of these adults and 2/8 of these children, the symptoms mimicked FGID. The adult subgroup included patients with unspecified functional bowel disorder (n=9), functional bloating (n=7), and IBS (n=5), and the child subgroup included patients with abdominal migraine (n=1) and IBS (n=1). Among the 25 adults, 14 reported feeling full after a regular-size meal, and 12 complained of abdominal bloating/distension. All of the children with GI symptoms complained of low abdominal pain associated with changes in the form of the stool/improvements with defecation. In conclusion, according to Rome III criteria, the most frequent diagnoses of FGID among the adults with FD were unspecified functional bowel disorder, followed by functional bloating and IBS. The most frequent GI symptom in the children in our population was IBS-like abdominal pain, while the adults exhibited a full feeling following a regular-size meal and abdominal bloating/distension.